Rivaroxaban in patients with mechanical heart valves: A pilot study. Issue 186 (February 2020) - Roost, Eva; Weber, Alberto; Alberio, Lorenzo; Englberger, Lars; Reineke, David; Keller, Dorothée; Nagler, Michael; Carrel, Thierry
Abstract: Background: Patients with mechanical heart valves are still not eligible for treatment with direct oral anticoagulants (DOAC). We aimed to conduct a proof-of-principle study investigating the anti-Xa inhibitor rivaroxaban as antithrombotic treatment in patients with recent mechanical aortic valve replacement. Materials and methods: Low-risk patients scheduled for elective mechanical aortic valve replacement were treated with rivaroxaban 20 mg once daily (OD) in a prospective cohort study, started on day 3 postoperatively and given for 6 months. The study was registered at ClinicalTrials.gov (#NCT02128841 ). Results: Ten patients were included (median age, 48; range 39 to 60). Indication was aortic valve stenosis in 6 patients, aortic root aneurysm with severe aortic valve regurgitation in 3 patients, and mixed stenosis/regurgitation in 1 patient. Neither thromboembolic nor bleeding events were observed, and no patient died. Absence of valve thrombosis was demonstrated in all patients. On day 7, median D-dimers were 2723 μg/L (inter-quartile range [IQR] 1672, 5695 μg/L), median TAT levels were 4.5 μg/L (IQR 4.1, 5.6 μg/L); and median peak thrombin generation was 150 nM (IQR 91, 183). On day 90, median D-dimers were 426 μg/L (IQR 278, 569), median TAT levels were 2.7 μg/L (IQR 2.2, 3.1), and median peak thrombin generation were 66 nM (IQR 62, 87). Conclusions: Rivaroxaban 20 mg OD was safe and effective in a pilot study of 10 low risk patients with mechanical aortic heart valve. Our results justify larger studies investigating the application of anti-Xa inhibitors in patients with mechanical heart valves. Highlights: Direct oral anticoagulants are still not applicable to patients with mechanical heart valves. We conducted a proof-of-principle pilot study using rivaroxaban 20 mg OD in 10 patients. Rivaroxaban was safe and effective in low risk patients with mechanical aortic heart valve. Our results justify larger studies in this population.